Monazite as a control on Th/U in magmatic zircon - Pineda, Camila; Schmitt, Axel Karl; Morata, Diego (Chemical geology, 2022)
Zircon is one of the most widely studied minerals for geochronology, and it has been successfully used to determine the age of young eruptions (< 300 ka) through U-Th dating. However, the processes leading to Th/U variations between cogenetic zircon crystals that are often much larger than expected from partitioning considerations are still not fully understood, despite the critical importance of zircon Th/U variability for isochron dating, for the disequilibrium correction of radiometric ages, and for identifying different zircon generations. Here, we present 238U-230Th disequilibrium ages and trace element abundances of zircon from the Quaternary Pudahuel Ignimbrite, a caldera-forming eruption associated to the Maipo volcanic complex in central Chile. Zircon chemical signatures show a decrease of Th/U along with decreasing Ti-in-zircon temperatures that can be related to the presence of accessory minerals which incorporate Th over U into its structure. These variations can also be identified along individual depth profiles, suggesting that monazite co-crystallization is the key cause for a sharp rimward decrease in zircon Th/U. Apatite fractionation is expected to have little impact on Th/U in the remaining melt, and in consequence U-Th activity ratios in zircon because it mostly saturates at temperatures above zircon saturation, and partitioning differences between Th and U are minor. By contrast, monazite fractionation strongly controls Th/U in Pudahuel rhyolite melts, especially at low temperatures. The isochron age calculated from zircon with low Th/U (238U/232Th activity >5.2) crystallized at low temperature below monazite saturation (167 ± 8 ka; 1σ error) is younger than for zircon with high Th/U (238U/232Th < 5.2). This presents the most precise age constraint available for Pudahuel Ignimbrite, albeit as a maximum eruption age. These results are particularly important in the study of young eruptions, where accurate ages are important to reliably interpret eruptive recurrence and volcanic chronostratigraphy, which in turn can affect the hazard awareness of volcanic systems.
Gesehen am 14.07.2022